2015
DOI: 10.1007/s00531-015-1144-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of sediment composition and behavior under dynamic loading conditions on slope failure initiation: a study of a subaqueous landslide in earthquake-prone South-Central Chile

Abstract: Subaqueous slope failure mechanisms are still poorly understood partly because they are difficult to study due to the remote location of submarine landslides. Landslides in lakes are smaller in size and more readily accessible and therefore represent a good alternative to their marine counterparts. Lake Villarrica, located in South-Central Chile, experienced significant slope failure and serves here as an exemplary study area for subaqueous landslide initiation mechanisms in tectonically active settings. Corin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…During the testing procedure axial strain, vertical load (σ n ), cell pressure (σ c ) and pore water pressure were monitored and recorded (for more detail see Wiemer et al, 2015).…”
Section: Dynamic Triaxial Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the testing procedure axial strain, vertical load (σ n ), cell pressure (σ c ) and pore water pressure were monitored and recorded (for more detail see Wiemer et al, 2015).…”
Section: Dynamic Triaxial Experimentsmentioning
confidence: 99%
“…The cylindrical specimens had a circular area of 0.001 m 2 and a height of 75 mm ± 3 mm. The specimens were assembled in a Stenzel triaxial cell (for technical details refer to Wiemer et al (2015)). …”
Section: Dynamic Triaxial Experimentsmentioning
confidence: 99%
“…This high sensitivity of Lago Inferiore to earthquake shaking may be explained by many factors like slope angle, sediment thickness or geotechnical properties of the sedimentary succession (e.g. Morgenstern, 1967;Strasser et al, 2011;Ai et al, 2014;Wiemer et al, 2015). However, Wilhelm et al (2016b) suggested that the dominant factor explaining the lake sensitivity of such Alpine lakes is the sedimentation rate, i.e.…”
Section: Earthquake Record and Lake Sensitivitymentioning
confidence: 99%
“…Fresh volcanic fall-out ashes have been suggested or identified as glide planes of submarine landslides (e.g. Harders et al 2010;Expedition 340 Scientists 2012;Sassa et al 2012;Strasser et al 2012;Laberg et al 2014;Wiemer et al 2015), where earthquaketriggered liquefaction (Castro 1975) was argued to be the most likely sediment failure mechanism. The submarine landslide community currently debates on whether fresh volcanic fallout ash may act as 'induced weak layer' as defined in Locat et al (2014).…”
Section: Introductionmentioning
confidence: 98%